The Condition of Coral Reefs Ecosystem in Poncan Gadang Island Sibolga City and Management Efforts - Rahman Muda Maulana; Miswar Budi Mulya; T. Alief Aththorick (TALENTA Publisher, Universitas Sumatera Utara, 2025)
Poncan Gadang Island is one of the islands in Sibolga City. The island is utilized by the community for various activities, such as beach tourism, underwater tourism and capture fisheries. This study aims to assess the coral reef condition of Poncan Gadang Island and provide recommendations for its management efforts. The research was conducted in February 2023 using the Underwater Photo Transect method to assess coral cover. The Underwater Photo Transect method was selected for its ability to provide permanent photographic records for further analysis, comparison over time and efficiency in capturing large- scale coral conditions. Management recommendations were analyzed using the SWOT analysis method. SWOT analysis was selected because provided a structured framework for management decision-making. The results indicated that the average percentage of live coral cover was 24.01%, classifying the coral reefs as damaged condition. This degradation is likely influenced by anthropogenic activities and environmental stressors. Based on the SWOT analysis, it is recommended that Poncan Gadang Island’s management address internal weakness to mitigate external threats. The SWOT analysis shows that management efforts should focus on addressing internal weaknesses, such as inadequate of local awareness and conservation policies to counteract external threats like unsustainable tourism practices and climate change. Implementing stricter tourism regulations, community- based conservation efforts and coral reef restoration for enhance reef resilience.